Grain nutritional and antioxidant profiling of diverse lentil (Lens culinaris Medikus) genetic resources revealed genotypes with high nutritional value - Riaz, Fareeha; Hameed, Amjad; Asghar, Muhammad Jawad (Frontiers in Nutrition, 2024)
The lentil (Lens culinaris Medikus ssp. Culinaris) is a self-pollinating, diploid (2n = 2X = 14) crop with a genome size of 4 Gbp. The present study was conducted to provide a database for the evaluation of lentil antioxidant capacity, nutritional quality, and biochemical attributes. For these purposes, lentil germplasm, including 100 exotic and local genotypes from different agro-climatic zones of Pakistan, was collected. Significant variation (p < 0.05) was found among the genotypes under investigation using the Tukey HSD test. Ascorbate peroxidase was highest in ALTINOPARK (2,465 Units/g s. wt.), catalase in LPP 12110 (5,595 Units/g s. wt.), superoxide dismutase in LPP 12105 (296.75 Units/g s. wt.), and peroxidase in NIAB Masoor 2002 (3,170 Units/g s. wt.). Furthermore, NLM 15016 had a maximum total antioxidant capacity of 15.763 mg/g s. wt. The maximum values of total soluble sugars (83.93 mg/g. s. wt.) and non-reducing sugars (74.79 mg/g. s. wt.) were noticed in NLM 15015. The highest reducing sugars were detected in ILL 8006 (45.68 mg/g. s. wt.) ascorbic acid in LPP 12182 (706 μg/g s. wt.), total phenolic content in NLI 17003 (54,600 μM/g s. wt.), and tannins in NLI 17057 (24,563 μM/g s. wt.). The highest chlorophyll a (236.12 μg/g s. wt.), chlorophyll b (317 μg/g s. wt.), total chlorophyll (552.58 μg/g s. wt.), and lycopene (10.881 μg/g s. wt.) were found in NLH 12097. Maximum total carotenoids were revealed in the local approved variety Markaz 2009 (17.89 μg/g s. wt.). Principal component analysis (PCA), correlation analysis (Pearson’s test), and agglomerative hierarchical clustering (AHC) were performed to detect the extent of variation in genotypes. In cluster analysis, all genotypes were categorized into three clusters. Cluster II genotypes showed remarkable divergence with cluster III. According to PCA, the contribution of PC-I regarding tested nutritional parameters toward variability was the highest (39.75%) and indicated positive factor loading for the tested nutritional and biochemical parameters. In conclusion, genotype X 2011S 33–34-32 can be used by the food industry in making pasta, multigrain bread, and snacking foods due to its high protein content for meat alternative seekers. Identified genotypes with high nutritional attributes can be utilized to improve quality parameters in the respective lentil breeding lines.